Compact microstrip reconfigurable filter based on spiral resonators. Issue 2 (26th November 2018) - Donelli, Massimo; Manekiya, Muhammedhusen; Menon, Sreedevi K.
Abstract: In this work, the design of a reconfigurable stop‐band filter based on a set of spiral microstrip resonators is proposed. In particular, a set of spiral resonators able to reject different Wi‐Fi channels are activated or deactivated by means of electronic switches based on pin diodes. A filter prototype composed of five resonating elements and coupled with a microstrip was fabricated and experimentally assessed. Good performances have been verified experimentally, with reference to the filter reject capabilities. The numerical and experimental results are in good agreement.